Nothing is free: A survey of the social cost of the main payment instruments in Hungary - Anikó Turján; Éva Divéki; Éva Keszy-Harmath; Gergely Kóczán; Kristóf Takács (Magyar Nemzeti Bank, 2011)
The study applies two approaches for the estimation of the social costs of main payment instruments (cash, debit card and credit card transactions, credit transfers, direct debits, business-to-business direct debits, postal inpayment money orders, postal outpayment money orders for pensions) used in Hungary in 2009. The first approach is based on the current payment structure, while the second approach is based on a more modern, hypothetical payment structure involving less cash, with no use of paper-based methods. In the first approach, the social cost amounts to HUF 388 billion, i.e. 1.49% of the GDP, while in the second approach, such cost amounts to HUF 85 billion, i.e. 1.09% of the GDP. In this context, social cost means the use of all resources (time, materials and money) necessary for the execution of payments, calculated as a net value (i.e. exclusive of fees paid for payment services). Thus, HUF 103 billion could be saved in social costs if the use of payment instruments were to be modified.
Keywords: D12; D23; D24; 330; private cost; social cost; net private cost; unit cost; social savings; cash transactions; debit card transactions; credit card transactions; paper-based credit transfers; electronic credit transfers; direct debits; business-to-business direct debits; postal inpayment money orders; postal outpayment money orders for pensions; Zahlungsverkehr; Kosten; Ungarn